Does fortification of pasteurized donor human milk increase the incidence of necrotizing enterocolitis among preterm neonates? A randomized controlled trial. (2nd October 2019) - Adhisivam, Bethou; Kohat, Dilesh; Tanigasalam, Vasanthan; Bhat, Vishnu; Plakkal, Nishad; Palanivel, C.
Abstract: Objective: To compare the effect of fortified pasteurized donor human milk (PDHM) versus unfortified PDHM on the incidence of necrotizing enterocolitis (NEC) and immediate outcome among preterm neonates. Methods: This randomized controlled trial (RCT) conducted in a tertiary care teaching hospital, south India included 80 healthy preterm neonates randomized to two groups (Group A and B). Neonates in Group A and B were fed with fortified PDHM and unfortified PDHM, respectively. Neonates in both groups were managed uniformly as per standard NICU protocol. The primary outcome was the incidence of NEC and the secondary outcomes included severity of NEC, incidence of sepsis, mortality, duration of hospital stay, number of days to reach full enteral feeds and weight gain. Neonates were followed up for 28 days or discharge whichever was earlier. Results: The baseline maternal and neonatal characteristics in both groups were comparable. There was no increase in incidence of NEC in fortified PDHM group compared to unfortified PDHM group (2.5 versus 7.5%, p  = .31). Severity of NEC, incidence of sepsis, mortality, duration of hospital stay, number of days to reach full enteral feeds and weight gain were also similar in both groups. Conclusions: Standard fortification of PDHM does not increase the incidence of NEC among preterm neonates.